Indikator Penciri Penanggalan Hijriah pada Pergerakan Pasang Surut - Salnuddin Salnuddin (Universitas Islam Negeri Jakarta, 2017)
Rhythmic movement of the tides follow the movement of the moon,as the dominant component of which has a rhythmic, should the movement of tidal inform month trip in the form of style variations of tide generating force (GPP) which indicates the time in the Hijra calendar. This article aims to determine the indicator of the tidal movement indicating the time of the Hijri calendar. The timing of slack water (t sw) the movement receded into pairs (tsw s) in peak II relatively consistent for the three months of data were analyzed tidal movement. Consistency is shown on the results of the statistical analysis by comparing the Probability (Pr) to the Wilks’ Lambda ( ) is very small(<0.0001) which means that the time of slack water (t sw) can be a primary identifier in determining the Hijra calendar. Further research is needed to determine the time point t SWS belt of a general nature in order to facilitate the determination of the Hijra calendar through the movement of the tides.DOI: 10.15408/ajis.v17i2.5686